A Descriptive Study to Assess the Effectiveness of Instructional Modules on Knowledge Regarding Challenges Faced by Rural Community People on Cancer Preventive Measures Among People Living in the Selected Community Area, Palakkad District - Zaina Jose Elizabeth; Srinivasan G.; Rose Jose; Nowfel P.M.; Shincy. K. (International Journal of Oncological Nursing and Practices, 2024)
This study employed a quantitative approach with a descriptive study design to assess the knowledge and challenges faced by rural communities regarding cancer preventive measures. A total of sixty participants were selected using purposive sampling, which is non-probability based. Data were gathered through a semi-structured questionnaire to capture demographic information, alongside a structured questionnaire specifically designed to evaluate knowledge on cancer prevention challenges within the rural population. The collected data were analyzed using both descriptive and inferential statistics. The findings highlighted significant insights into the knowledge levels regarding cancer prevention among the respondents. In the pre-test assessment, 33.33% of participants exhibited poor knowledge, while 66.6% demonstrated average knowledge regarding cancer prevention measures. Following an educational intervention, the post-test results indicated a notable improvement, with 75% of respondents showing average knowledge and 25% achieving good knowledge in cancer prevention strategies. Additionally, the correlation analysis revealed a positive relationship in knowledge levels concerning cancer prevention between male and female participants, suggesting that gender may play a role in knowledge acquisition about cancer preventive measures. This study underscores the necessity of targeted educational programs to enhance awareness and understanding of cancer prevention in rural communities, ultimately aiming to improve health outcomes. The results suggest that educational interventions can significantly elevate knowledge levels, thereby empowering individuals in rural areas to adopt effective cancer prevention strategies. Further research is recommended to explore the long-term impact of educational initiatives on health behaviors in these communities.
Keywords: Cancer preventive measures; a structured questionnaire; behaviors; educational initiatives; knowledge levels